Jewish and Christian communal identities in the Roman world - Fursṭenberg, Yaʾir (Ancient Judaism and early Christianity, 2016)
Preliminary Material -- Introduction: The Shared Dimensions of Jewish and Christian Communal Identities /Yair Furstenberg -- The Ptolemaic and Roman Definitions of Social Categories and the Evolution of Judean Communal Identity in Egypt /Sylvie Honigman -- The Roman State and Jewish Diaspora Communities in the Antonine Age /Martin Goodman -- Civic Identity and Christ Groups /John S. Kloppenborg -- Organized Charity in the Ancient World: Pagan, Jewish, Christian /Pieter W. van der Horst -- The Fourth Book of Maccabees in a Multi-Cultural City /Tessa Rajak -- Rome and Alexandria: Why was there no Jewish Politeuma in Rome? /Daniel R. Schwartz -- From Text to Community: Methodological Problems of Reconstructing Communities behind Texts /Jörg Frey -- Lycaonian Christianity under Roman Rule and their Jewish-Christian Tradition /Cilliers Breytenbach -- The Jewish Community in Egypt before and after 117 ce in Light of Old and New Papyri /Tal Ilan -- Jewish Communities in the Roman Diaspora: Why Salo Baron Still Matters? /Seth Schwartz -- “You are a Chosen Stock . . .”: The Use of Israel Epithets for the Addressees in First Peter /Lutz Doering -- Author Index -- General Index.